PENGARUH CONCERN TO ORDER DAN CUSTOMER ORIENTATION TERHADAP DISIPLIN KERJA PEGAWAI KANTOR REKTORAT UNIVERSITAS UDAYANA - Aryawati, Ni Luh Gede; Riana, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.08. TAHUN 2016, 2016)
Discipline of Civil Servants (PNS) is always in the spotlight of the public who are users of its services. This condition is a persistent challenge and dilemma for the state apparatus. The study, titled influence concern to order and customer orientation to employee discipline Udayana University Rectorate use 129 employees as the study sample. Test equipment used to test the hypothesis is multiple linear regression model to test for normality, multicollinearity test and test heterocedastisity as classical assumptions. Hypothesis test showed that there is a positive and significant effect either by the concern to order and customer orientation to employee discipline Rectorate of Udayana University. Implementation of the results of the test course is to increase the quality of both these aspects. Focus increase for concern to order is the proper understanding of the duties and responsibilities of employees. Improving the quality of customer orientation is directed at developing the ability to use information systems strategy.
Keywords: discipline, concern to order and customer orientation